2009
DOI: 10.1007/s12245-008-0080-9
|View full text |Cite
|
Sign up to set email alerts
|

Demographics of toxic exposures presenting to three public hospital emergency departments in Singapore 2001–2003

Abstract: BackgroundThe demographics of poisoned patients and the circumstances of toxic exposure have not been evaluated in Singapore for the last 10 years.AimThis study aims to give an estimate of the burden of poisoning in Singapore from the emergency department’s (ED) perspective.MethodA retrospective study of toxic exposure was conducted over a period of 3 years from 2001 to 2003 at the ED of three public hospitals, one being a paediatric hospital.ResultsThere were 9,212 cases of toxic exposures during the study pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 11 publications
1
25
1
Order By: Relevance
“…On the basis of a previous study, we estimate that there could be about 450 admissions for toxic exposures per year in our hospital 1. Admissions to our EDOU would have constituted about 30% of this cohort.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…On the basis of a previous study, we estimate that there could be about 450 admissions for toxic exposures per year in our hospital 1. Admissions to our EDOU would have constituted about 30% of this cohort.…”
Section: Discussionmentioning
confidence: 85%
“…Hollander et al found that 90% of poisoned patients managed in an observation unit could be medically cleared after 6 hours 5. In addition, a multicentre study in Singapore found that a third of patients admitted for poisoning stayed less than 24 hours 1. Together, these findings suggest that many patients with poisoning could potentially be managed in a short-stay observation unit.…”
Section: Introductionmentioning
confidence: 99%
“…(3,4) In previous retrospective studies conducted in Singapore, paracetamol was identified to be the most common pharmaceutical agent implicated in toxic exposure and self-poisoning, accounting for 55% of suicide overdose attempts among youths below 21 years of age. (5,6) Specifically among the paediatric population, outcomes of paracetamol overdose appeared to be favourable, with no significant morbidity or mortality, as observed in a case series. (7) However, given that the majority of patients in that study were aged five years or younger, no inference can be drawn with regard to the profile of paracetamol overdose cases in the local adult population.…”
Section: Introductionmentioning
confidence: 80%
“…The ethnic distribution in our cohort closely mirrors the distribution observed in a retrospective evaluation of toxic exposures conducted in a local setting ten years ago. (5) The majority of paracetamol overdose cases were intentional and involved acute ingestion, suggesting that paracetamol overdose would be difficult to prevent with measures solely targeted at enhancing public awareness. However, the perceived lack of lethality in almost half of our patients who ingested a potentially toxic dose of paracetamol reflects a certain knowledge gap within the local population.…”
Section: Discussionmentioning
confidence: 99%
“…Cobra bites are common in Peninsular Malaysia and require significant medical intervention [3, 4]. However, snake bites are considered uncommon in largely urban Singapore [5, 6]. …”
Section: Introductionmentioning
confidence: 99%